Selective Inhibition of Histone Deacetylase Class IIa With MC1568 Ameliorates Podocyte Injury - He, Xu; Sun, Tao; Zhang, Pei; Xia, Zhengkun; Gao, Chunlin; Ren, Hongqi; Ji, Daxi (Frontiers in Medicine, 2022)
Histone deacetylases (HDACs) inhibitors are promising therapeutic agents against proteinuric kidney diseases, here, we investigated the effect of MC1568, a selective inhibitor of HDAC class IIa, on the development and progression of nephrotic syndrome in a murine model induced by Adriamycin (ADR). In kidney tissues of FSGS patients, all 4 members of HDAC IIa were significantly upregulated in podocytes. In ADR-treated cultured human podocyte, expression of HDAC IIa were induced, meanwhile inhibition of HDAC IIa with MC1568 restored cytoskeleton structure and suppressed expression of desmin and α-SMA. In mice, administration of MC1568 at 14 days after ADR ameliorated proteinuria and podocyte injury, also decreased expression of Fibronectin and α-SMA. Mechanistically, MC1568 inhibited ADR induced β-catenin activation in vitro and in vivo. Together, these finding demonstrate that HDAC IIa inhibition ameliorates podocyte injury and proteinuria, which provide a possibility that MC1568 may be used in nephrotic syndrome.